Teologi Kesehatan: Aklimatisasi dan Deponeren Penggunaan Gadget Dalam Ibadah dan Misi Gereja Berdasarkan I Korintus 3:17 - Froland Pangajow; Bartolomeus Nainggolan; Stimson Hutagalung (Jurnal Ilmiah Wahana Pendidikan, 2022)
The Covid-19 virus pandemic has changed the order of people's lives, especially church members. This change presents an acclimatization of a new habit where digital media, especially gadgets, are considered as the main alternative in the implementation of online worship to reach the people. But in reality, people are unwittingly faced with serious problems, because the impact of electromagnetic wave radiation is very risky to health if used beyond a certain threshold or tolerance. This study aims to provide an understanding of the importance of health and encourage the church to play an active role in fortifying the people against the negative impacts of complex radiation of electromagnetic waves, from a biblical perspective in I Corinthians 3:17. By using qualitative _descriptive method in the form of literature review which refers to the situation that is currently happening and is expected to continue. In the end, the church can broaden the understanding to the people of the importance of using digital media properly without worrying about the potential adverse effects on health